ACARA SURVIVAL IDOLA DI ASIA TIMUR: SEJARAH DAN DAMPAKNYA SEBAGAI FENOMENA GLOBAL - Rifqiaulian, Tegar (UI Scholars Hub, 2025)
Idol survival shows are competition-based reality programs in which participants compete through various vocal, dance, and rap challenges to debut in a new idol group. In recent years, this genre has experienced a significant rise in popularity across East Asia. The phenomenon of idol survival shows has become a driving force behind the global popularity of Asian music, particularly within the realms of K-Pop, J-Pop, and C-Pop. This article explores the history, format, and factors contributing to the success of idol survival shows, as well as discusses their impact and controversies. The study finds that the phenomenon originated in South Korea, pioneered by programs such as Produce 101, and spread throughout East Asia through format adaptations. Its popularity is fueled by a unique format that involves active audience participation and interaction. While the genre has had positive impacts, this article also highlights ethical issues, including result manipulation scandals, participant exploitation, and unhealthy fan behavior.